Review of Facilities for Low-Income Countries. (Policy Papers; Policy Paper ;, 2012)
The 2009 reforms have broadly achieved their objective of closing gaps and creating a streamlined architecture of facilities that is better tailored to the diverse needs of LICs. Supported by the financing package to boost the PRGT's lending capacity for 2009-14 and the accompanying doubling of access, the Fund was able to mount an effective response to LICs' needs during the global financial crisis.